Canine Cancer: Strategies in Experimental Therapeutics - Thamm, Douglas H. (Frontiers in Oncology, 2019)
Cancer is the leading cause of death in adult dogs. There are many features about spontaneously developing tumors in pet dogs that contribute to their potential utility as a human disease model. These include similar environmental exposures, similar clonal evolution as it applies to important factors such as immune avoidance, a favorable body size for imaging and serial biopsy, and a relatively contracted time course of disease progression, which makes evaluation of temporal endpoints such as progression free and overall survival feasible in a comparatively short time frame. These criteria have been leveraged to evaluate novel local therapies, demonstrate proof of tumor target inhibition or tumor localization, evaluate potential antimetastatic approaches, and assess the safety, efficacy and immune effects of a variety of immune-based therapeutics. Some of these canine proof of concept studies have been instrumental in informing subsequent human clinical trials. This review will cover key aspects of clinical trials in dogs with spontaneous tumors, with examples of how these studies have contributed to human cancer therapeutic development.